Comparison Analysis of Digital Forensic Tools on Instagram Messenger using The National Institute of Standards and Technology (NIST) Method - Harno Supardin; Satra, Ramdan; Asis, Muh. Arfah; Teng, Ming Foey (Bulletin of Social Informatics Theory and Application, 2022)
Technological developments from time to time are very rapid, one of which is the development of smartphones which are always evolving in terms of operating systems, features, specifications, and applications. Today's increasingly sophisticated technology has become an important part of people's lives, some activities of people's lives can be carried out by utilizing technology, including committing crimes in cyberspace. One of the most widely used social media applications is Instagram. Instagram messenger causes cybercrime, pornography, fraud and cyberbullying. This study aims to compare the performance of digital forensic tools in obtaining digital evidence on Instagram messenger using the NIST Method. The results of this study indicate that MOBILedit Forensic and Magnet Axiom have the following accuracy results in restoring deleted data on Instagram messenger, MOBILedit Forensic 69.23% and Magnet Axiom 76.92%.